74.0k views
0 votes
I need help with this question please.Fyi this is a part of a homework practice

I need help with this question please.Fyi this is a part of a homework practice-example-1
User FJam
by
5.5k points

1 Answer

3 votes

Since the polynomial has to be the simplest, it must be of the form:


P(x)=(x+2)(x-4)(x-5)\text{.}

Multiplying the binomials we get:


\begin{gathered} P(x)=(x^2-2x-8)(x-5) \\ =x^3-5x^2-2x^2+10x-8x+40. \end{gathered}

Simplifying the above polynomial we get:


P(x)=x^3-7x^2+2x+40.

Answer:


P(x)=x^3-7x^2+2x+40.

User Gratzy
by
5.1k points